2016
DOI: 10.1002/14651858.cd011586.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and antiseptics for pressure ulcers

Abstract: The relative effects of systemic and topical antimicrobial treatments on pressure ulcers are not clear. Where differences in wound healing were found, these sometimes favoured the comparator treatment without antimicrobial properties. The trials are small, clinically heterogenous, generally of short duration, and at high or unclear risk of bias. The quality of the evidence ranges from moderate to very low; evidence on all comparisons was subject to some limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 105 publications
0
67
0
4
Order By: Relevance
“…Even though several studies addressed this issue over the past years most concluded that further comprehensive analyses are needed to install clear and individual recommendations for the use of antimicrobial dressings. 10,12,13,17,22 In terms of in vitro test settings experimental designs are often limited to a restricted selection of available dressings or fail to take into account the specific biological wound milieu. 23,24 This generates inconsistent data and complicates translation of results into clinical settings and study designs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though several studies addressed this issue over the past years most concluded that further comprehensive analyses are needed to install clear and individual recommendations for the use of antimicrobial dressings. 10,12,13,17,22 In terms of in vitro test settings experimental designs are often limited to a restricted selection of available dressings or fail to take into account the specific biological wound milieu. 23,24 This generates inconsistent data and complicates translation of results into clinical settings and study designs.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of studies have been conducted in vitro as well as in vivo in the past to investigate the antiseptic efficacy, cytotoxicity, and clinical applicability of such formulations. Nevertheless, the range of available products, especially in case of antiseptic dressings, is wide and the correct choice for the individual setting can be difficult and a general consensus could not be reached so far . Even though several studies showed a benefit of antiseptic formulations regarding prevention and treatment of local wound infection, no overall improvement in healing rates of chronic wounds can be postulated so far .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, most treatment protocols would recommend the use of intravenous antibiotics when there is evidence of osteomyelitis, but there is actually little evidence for its use. 38,39 Generally, osteomyelitis requires debridement of the infected bone and coverage with a well-perfused flap to allow it to heal. 40 Topical antibiotics have little role in the management of pressure ulcers.…”
Section: Infection Controlmentioning
confidence: 99%